Cover Image. Issue 3 (10th June 2019) - Gong, Junbo; Kong, Yifan; Li, Jianmin; Wang, Xiangqi; Que, Yande; Zhang, Zengming; Ding, Zejun; Xiao, Xudong
Abstract : The cover image is based on the Research Article Role of surface microstructure of Mo back contact on alkali atom diffusion and Ga grading in Cu(In, Ga)Se2 thin film solar cells by Junbo Gong et al., DOI:10.1002/ese3.304 .